Budaya Akademik dan Integrasi Nilai Keislaman dalam Pendidikan Tinggi Islam: Studi Kasus di IAI Asshiddiqiyah Lempuing OKI - Ahmad Rojali; Abdullah Idi; Karoma; Yulia Tri Samiha (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This research is motivated by the importance of understanding Islamic education in higher education not only as a process of transmitting religious knowledge, but as a social practice that shapes academic culture, pedagogical interactions, Islamic identity, and moral responsibility of students. This research aims to analyze academic culture and the integration of Islamic values in Islamic higher education. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation, then analyzed thematically-interpretively. The results of the study show that the integration of Islamic values takes place through six main forms, namely the formation of a religious academic culture, lecturer-student interaction as a medium for socializing values, a forum for academic-religious studies and activities, student awards and participation, Islamic education's response to social change, and a hidden curriculum in the formation of Islamic habitus. The values of manners, trust, discipline, responsibility, religiosity, respect for knowledge, and academic ethics are not only taught formally, but also habituated through campus symbols, lecturer examples, institutional routines, and daily social practices. This research confirms that Islamic universities function as a social space that simultaneously produces students' values, identity, academic culture, and moral orientation.